Inovasi Badan Usaha Milik Desa (BUMDES) Balaroa Pewunu - Firdayanti Bido; Mohammad Zeylo Auriza; Maskuri Sutomo (Jurnal Visi Manajemen, 2023)
Innovation is a system of recognition, development and renewal process that enhances economic success for entrepreneurs or producing companies and their consumers as well as the wider organization. BUMDes is one of the institutions that can be mobilized to support the improvement of the community's economy in the village. BumDes Balaroa Pewunu itself is engaged in the business of buying and selling agricultural products and savings and loans. Community economic empowerment is an effort to develop self-sufficiency and community welfare by increasing knowledge, attitudes, skills, behavior, abilities, and awareness, by utilizing existing resources. The stages of implementing the community service program are observation, interviews, proposals, data collection, training and reporting of the results of community service. In implementing the MBKM activities to Build Villages by conducting Socialization and Training inviting Resource Persons from the Faculty of Economics and Business, Tadulako University, Agriculture Lecturers. The activity was carried out in two days, the material on the first day was that the lecturer from the Faculty of Economics and Business presented a business plan, financial management. On the second day the lecturer from Agriculture presented material on the procedures for making organic fertilizer by utilizing existing materials around the village, participants who were present were the Village Government, Head of Bumdes, farmers. Through the training which was carried out by inviting expert Lecturers from FEB UNTAD and Faculty of Agriculture opening the insights of the Village Government, especially BUMDes to continue to improve BUMDes innovation as an effort to improve the village economy of Balaroa Pewunu